"That which is crooked can be made straight": Challenges and opportunities of Assistive Reproductive Technologies (ART) in Ireland in the 21st century. (1st December 2019) - King, Rob; Nagy, Andrea; Dempsey, Maria; Rice, Aoife
Abstract: Objective: Technology offers new opportunities, and challenges of as yet undreamed. Ethical intuitions honed over millions of years of small-group, competitive obligate sexual reproduction may mislead us in relation to new technologies. Between 1999 and 2008 the number of ART treatment cycles increased by 265% in Ireland. Some of the implications of such technologies are profound—challenging existing reproductive understanding. Ireland offers unique opportunities for study as a small country, emerging from a traditional religious past, with almost unregulated access to Assistive Reproductive Technology (ART). Method: Data from an Irish population of varied ages and both sexes ( N = 606) were collected through an on-line survey which included demographics and attitudes and knowledge of ART. Results: While interest in ART was high, accurate knowledge was patchy. Latent class analysis revealed a typology of five groups of responders to ART, distinguished by their attitudes and knowledge of this technology. These groups were tentatively labelled as 'Worried Yet Willing', 'Live and Let Live', 'Disengaged', 'Judgemental' and 'Conflicted'. This is a large, demographically representative sample from a country—Ireland—that is actively considering reproductive challenges in the twenty first century. This is therefore a valuable opportunity to access the processes underlining attitudes to these new opportunities and threats. However, even though the sample was reasonably large, women were—perhaps unsurprisingly—over represented. They outnumbered men by 4:1. Follow up research might specifically focus on males, and especially males in certain key demographic sectors. Conclusion: Responses to the introduction of ART in Ireland fell into five distinct groups. These groups had some predicative value in highlighting attitudes to ART provision in prospective groups, though not always in expected ways. Attitudes were generally positive. Understanding the distinguishing features of these types of responders is important for health care professionals regarding service development and delivery. Implications for the direction of future related research is discussed.